(untitled) (American Journal of Islam and Society, 2021)
• Remaking Muslim Lives: Everyday Islam in Postwar Bosnia and Herzegovina (by David Henig) • Lived Islam: Colloquial Religion in a Cosmopolitan Tradition (by Kevin Reinhart)